2011
DOI: 10.1182/asheducation-2011.1.136
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Residual Disease and Discontinuation of Therapy in Chronic Myeloid Leukemia: Can We Aim at a Cure?

Abstract: Patients with chronic myeloid leukemia (CML) who have achieved a complete molecular response (CMR) defined by no detectable BCR-ABL mRNA on imatinib (IM) treatment often ask whether it is necessary for treatment to continue. We now know that approximately 40% of patients with a stable CMR for at least 2 years are able to stop IM treatment and remain in molecular remission for at least 2 years. This exciting observation has raised hopes that many patients can be cured of CML without the need for transplantation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 64 publications
1
27
0
Order By: Relevance
“…In AML, it has been reported that [94][95][96][97] . Conversely, in chronic phase CML, the persistence of a detectable (that is, substantial) population of primitive (presumably pre-malignant) CML stem cells is not predictive of relapse 98 . Routine assays for MRD used clinically may, however, be unable to distinguish a new (often indolent or pre-malignant) subclone from the original dominant one.…”
Section: Evaluation Of Csc Eradicationmentioning
confidence: 98%
“…In AML, it has been reported that [94][95][96][97] . Conversely, in chronic phase CML, the persistence of a detectable (that is, substantial) population of primitive (presumably pre-malignant) CML stem cells is not predictive of relapse 98 . Routine assays for MRD used clinically may, however, be unable to distinguish a new (often indolent or pre-malignant) subclone from the original dominant one.…”
Section: Evaluation Of Csc Eradicationmentioning
confidence: 98%
“…[14][15][16]23,24,30,32,34,[37][38][39] Comparing patients in Table 1 (clinical trials) and Table 2 (case series), it is apparent that durable stable CMR before discontinuation is important to limit molecular relapse. Multivariate analyses have identified factors associated with molecular relapse and with prolonged TFR.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 All additional publications and abstracts addressing the topic of TKI discontinuation in CML directly were reviewed. [32][33][34][35][36][37][38] …”
Section: Methodsmentioning
confidence: 99%
“…Based on the sustained, deeper molecular responses observed in patients treated with TKIs, investigators became interested in the possibility of TFR. TFR studies have garnered interest among patients and physicians for various reasons, including the desire to avoid chronic low-grade adverse events and late-emerging toxicities, the potential for resistance, issues with compliance, safety concerns with pregnancy, cost, and patient motivation to live drug free [36]. Because data from TFR studies are still limited, TFR should currently be attempted only in the setting of a clinical trial, with strict molecular monitoring of patients [7,11].…”
Section: Importance Of Achieving Deep Molecular Responses To Tki Therapymentioning
confidence: 99%
“…Before the era of BCR-ABL1 TKIs, IFN with or without cytarabine was the most commonly used treatment in patients with CML [36]. Studies demonstrated that IFN conferred a survival advantage over conventional chemotherapy [37].…”
Section: Ifnmentioning
confidence: 99%